2016
DOI: 10.1109/mitp.2016.81
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Password Management Software: Toward Usable and Secure Enterprise Authentication

Abstract: Abstract-In today's corporate IT systems there is an undeniable pattern that is routinely repeated by employees: access to a huge number of password-protected services. In this regard, though deploying a strong enterprise password policy is a mean to increase security against online breaches and data leaks, it also imposes a significant usability burden for users. To alleviate this problem, Password Managers (PMs) are pointed out as user-friendly tools that automate the processes of password generation and log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
3
0
3
Order By: Relevance
“…Layanan tersebut mengharuskan pengguna untuk membuat akun terlebih dahulu agar mendapatkan akses. Semakin banyak layanan yang digunakan menyebabkan pengguna harus mengatur dan mengelola akun serta sandi di setiap layanan yang berbeda (Cabarcos et al, 2016).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Layanan tersebut mengharuskan pengguna untuk membuat akun terlebih dahulu agar mendapatkan akses. Semakin banyak layanan yang digunakan menyebabkan pengguna harus mengatur dan mengelola akun serta sandi di setiap layanan yang berbeda (Cabarcos et al, 2016).…”
Section: Pendahuluanunclassified
“…Selain itu, terdapat beberapa penelitian mengenai aplikasi pengelola kata sandi yang telah dilakukan sebelumnya. Penelitian tersebut yaitu penelitian oleh (Cabarcos et al, 2016) tentang analisis perbandingan keamanan dan kegunaan aplikasi 1Password, LastPass, KeePass, dan Dashlane berdasarkan NIST SP 800-57 part 1, rev. 4 dan Whitney Quesenbery, dengan hasil aplikasi 1Password memiliki kegunaan lebih unggul dibandingkan dengan aplikasi Lastpass, penelitian oleh (Schougaard et al, 2016) perbandingan kesesuaian fungsi dari beberapa aplikasi pengelola kata sandi pada platform cloud berdasarkan functional dan non-functional requirement, hasil yang didapatkan adalah aplikasi Vaultier memiliki tingkat kesesuaian fungsi yang lebih tinggi dibandingkan dengan aplikasi Lastpass dan aplikasi lainnya.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…A previous study [7] found that writing passwords down in a secure location or using password managers can be a promising solution for password reuse. Password managers offer the benefits of having strong passwords and uniqueness, compared to other entry methods [22], while they improve usability by offering autofill login forms [27]. Moreover, password managers generate, store and encrypt passwords, while users need only remember one master password [28]; Komanduri et al state that users create stronger passwords when they use memory aids, which can encourage them to use password managers [29].…”
Section: Related Workmentioning
confidence: 99%
“…Regarding the seven tasks in this study, the idea for these tasks comes from a pioneering study by Chiasson et al [10]. These tasks were also applied in another study [16,27]. The usability test has seven tasks because LastPass has many features and functions within it.…”
Section: Usability Test and Interview Studymentioning
confidence: 99%